GENERAL ASPECTS OF COLON CANCER SURGERIES - Dias Pacheco Annicchino Baptistella, Tiberio (Health and Society, 2021)
Colorectal cancer (CCR) is the third most common tumor in men and the second most common tumor in women, accounting for 10% of all tumor types worldwide. With an estimated 608,000 deaths each year, CCR is the fourth most common cause of cancer-related death worldwide. The clinical manifestations of colon cancer depend largely on the location of the tumor. There are some treatment options such as systemic chemotherapy and intraperitoneal chemotherapy, but they are not as effective. Surgical treatment can occur in different ways, here are presented three possible forms of surgery, as well as their associated risks. New options emerge as alternatives to improve the prognosis of the disease.